A new species of Xanthagaricus (Agaricaceae, Agaricales) from Lahore, Punjab, Pakistan - Javeed, Palvisha; Kiran, Munazza; Haqnawaz, Muhammad (Phytotaxa, 2024)
A new species, Xanthagaricus lahorensis, is described based on collections from the Lahore District, Pakistan. Morphological data and phylogenetic analyses based on nrITS & LSU supported that the species is undescribed earlier. Xanthagaricus lahorensis is characterized by olive–yellow pileus with olive squamules at center going outward, dull yellowish-brown stipe, rough surface without rhizomorphic mycelial mat, absence of annulus, small, lacrymoid, brown walled with olivaceous guttule basidiospores (on average 4.2 × 3.2 µm), clavate, obovoid basidia, obovoid, clavate to broadly clavate cheilocystidia, and presence of clusters of cylindrical caulocystidia. With this new species, seven Xanthagaricus species have been reported from Pakistan. A key to the Pakistani Xanthagaricus species is provided in addition to the new species’ full description, illustrations, and phylogenetic analysis results.